2020
DOI: 10.1002/ese3.777
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure arrangement on the thermal characteristics of Li‐ion battery pack in thermoelectric generator

Abstract: Approximately 40% of the energy in traditional cars is discharged into the air through exhaust gas, causing a lot of waste of thermal energy, leading to huge economic losses. 1-3 Thermoelectric generators (TEGs) are the devices that can convert thermal energy into electrical energy, which can effectively achieve energy recovery. 4,5 Usually, the recovered electric energy is stored through a battery pack and is supplied to the vehicle-mounted electrical equipment. 6 The battery management system, as the core of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The coolant inlet entrance velocity is prescribed at 0.21 kg/s, while the outlet acts as a pressure outlet, maintaining normal atmospheric pressure [41]. The battery serves as the heat source, with internal heat generation configured using a User-Defined Function (UDF) program within the FLUENT software [42,43].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The coolant inlet entrance velocity is prescribed at 0.21 kg/s, while the outlet acts as a pressure outlet, maintaining normal atmospheric pressure [41]. The battery serves as the heat source, with internal heat generation configured using a User-Defined Function (UDF) program within the FLUENT software [42,43].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The results show that, with the incorporation of the TEG presented, a fuel consumption savings and CO 2 emissions reduction of 0.53% can be achieved. Zhu 33 studies the related structural and thermal properties of vehicle exhaust thermoelectric power generation and lithium–ion battery energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…With different operating conditions, the control valve was used to adjust the opening of the two outlets, which greatly improved the controllability and flexibility of battery thermal management. In terms of battery arrangement, Zhu et al [ 22 ] considered three typical battery arrangements in the same battery module: equal arrangement, increasing arrangement, and decreasing arrangement. Then the study found that the temperature uniformity of the battery module in decreasing arrangement was the most uniform.…”
Section: Introductionmentioning
confidence: 99%